A Quantum-Chemical DFT Approach to Elucidation of the Chirality Transfer Mechanism of the Enantioselective Suzuki–Miyaura Cross-Coupling Reaction - Radomir Jasiński; Oleg M. Demchuk; Dmytro Babyuk (Journal of Chemistry)
The DFT calculations of the simplified model of the asymmetric Suzuki–Miyaura coupling reaction were performed at the M062x/LANL2DZ theory level at first. It was found that enantioselective reactions mediated by the palladium complexes of chiral C,P-ligands follow a four-stage mechanism similar to that proposed previously as one of the most credible mechanisms. It should be underlined that the presence of substituents in the substrates and the chiral ligand at ortho positions determines the energies of possible diastereoisomeric transition states and intermediates in initial reaction steps. This suggests that, in practice, a sharp selection of theoretically possible paths of chirality transfer from the catalyst to the product should have a place and, therefore, the absolute configuration of the formed atropisomeric product is defined and can be predicted.